Whalefall ebook A novel. - Kraus, Daniel (2023)
A USA TODAY BESTSELLER Named a Best Book of 2023 by Book Riot , Shelf Awareness , and NPR The Martian meets 127 Hours in this "astoundingly great" (Gillian Flynn, #1 New York Times bestselling author) and scientifically accurate thriller about a scuba diver who's been swallowed by an eighty-foot, sixty-ton sperm whale and has only one hour to escape before his oxygen runs out. Jay Gardiner has given himself a fool's errand—to find the remains of his deceased father in the Pacific Ocean off the coast of Monastery Beach. He knows it's a long shot, but Jay feels it's the only way for him to lift the weight of guilt he has carried since his dad's death by suicide the previous year. The dive begins well enough, but the sudden appearance of a giant squid puts Jay in very real jeopardy, made infinitely worse by the arrival of a sperm whale looking to feed. Suddenly, Jay is caught in the squid's tentacles and drawn into the whale's mouth where he is pulled into the first of its four stomachs. He quickly realizes he has only one hour before his oxygen tanks run out—one hour to defeat his demons and escape the belly of a whale. Suspenseful and cinematic, Whalefall is an "powerfully humane" (Owen King, New York Times bestselling author) thriller about a young man who has given up on life...only to find a reason to live in the most dangerous and unlikely of places.